If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(x + -3) = -52 Reorder the terms: 4(-3 + x) = -52 (-3 * 4 + x * 4) = -52 (-12 + 4x) = -52 Solving -12 + 4x = -52 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + 4x = -52 + 12 Combine like terms: -12 + 12 = 0 0 + 4x = -52 + 12 4x = -52 + 12 Combine like terms: -52 + 12 = -40 4x = -40 Divide each side by '4'. x = -10 Simplifying x = -10
| 5x+8=3x+58 | | -5.89x+7.5=2.18 | | -37+x=-6(7x-1) | | -5(4x+3)-9=-3(-3x+6) | | 2+3[4+2(2)]= | | 33*5*-2= | | 0.6a+4=10 | | 4y-20=12y+2 | | -5=12 | | 0.3x-0.9(6-x)=-1.2 | | 2r-(5-r)=13-2r | | 33*x*y= | | 24+4(z-4)=6z-2 | | 5y-8=y-22 | | 2(0.78+0.4x)=0.01x | | 14=(-2k)+3 | | 2m+1/2(m-4)=9 | | -9(4b+1)+(37b-6)=0 | | 7g+14-5=-8 | | 7times(10-3w)=5(15-4w) | | 7n-(5n-6)=18 | | 6*(x-5)*(x-2)-2*(x-3)*(x-4)*(x-2)=2*x*(x-3)*(x-4)*(x-5) | | x^2-9x-34=0 | | 3(7x+1)=21x+3 | | 7x(10-3w)=5(15-4w) | | -6(1-7x)=32+4x | | 2c+12=-6 | | 25n+6=10 | | 8-5y= | | 6x+x+7= | | 3u+35=8u | | -2y+5y=12 |